Theoretical Basis for Setting Baga Utsaha Druwen Traditional Village (BUPDA) as an Economic Institution for Traditional Village Communities in Bali - I Wayan Suarjana (Law Doctoral Community Service Journal, 2023)
Bali is one of the provinces that does not manage its economy with the strength of natural resources, but with the strength of cultural resources. Just like natural resources, culture as an economic resource needs to be cared for. From the point of view of the science of law, differences in the positions of the burdens and the benefits resulting from these assignments constitute injustice. The allocation of these functions does not necessarily result in the establishment of a fair (structured, programmed, routine and systematic) cultural development system that connects budget recipients with cultural development actors. This research uses normative research methods, normative legal research is a scientific research method to find the truth based on scientific logic from the normative side. As is well known, each traditional village in Bali has different village potentials ranging from potential in the fields of agriculture, plantations, fisheries/marine affairs, tourism, to other creative industries. The formation of BUPDA is the best strategy in managing the potential and assets of traditional villages in Bali. Traditional villages that have grown and developed for centuries and have rights of origin, traditional rights, and original autonomy rights to manage their own household, have made a very large contribution to the continuity of people's lives in the nation and state that need protection and empowerment. As a community economic institution, BUPDA receives legal and political protection both nationally and internationally in accordance with applicable laws and regulations.